The two clock proteins CCA1 and LHY activate VIN3 transcription during vernalization through the vernalization-responsive cis-element. Issue 3 (21st December 2021) - Kyung, Jinseul; Jeon, Myeongjune; Jeong, Goowon; Shin, Yourae; Seo, Eunjoo; Yu, Jihyeon; Kim, Hoyeun; Park, Chung-Mo; Hwang, Daehee; Lee, Ilha
Abstract: Vernalization, a long-term cold-mediated acquisition of flowering competence, is critically regulated by VERNALIZATION INSENSITIVE 3 ( VIN3 ), a gene induced by vernalization in Arabidopsis. Although the function of VIN3 has been extensively studied, how VIN3 expression itself is upregulated by long-term cold is not well understood. In this study, we identified a vernalization-responsive cis-element in the VIN3 promoter, VREVIN3, composed of a G-box and an evening element (EE). Mutations in either the G-box or the EE prevented VIN3 expression from being fully induced upon vernalization, leading to defects in the vernalization response. We determined that the core clock proteins CIRCADIAN CLOCK-ASSOCIATED 1 (CCA1) and LATE-ELONGATED HYPOCOTYL (LHY) associate with the EE of VREVIN3, both in vitro and in vivo. In a cca1 lhy double mutant background harboring a functional FRIGIDA allele, long-term cold-mediated VIN3 induction and acceleration of flowering were impaired, especially under mild cold conditions such as at 12°C. During prolonged cold exposure, oscillations of CCA1/LHY transcripts were altered, while CCA1 abundance increased at dusk, coinciding with the diurnal peak of VIN3 transcripts. We propose that modulation of the clock proteins CCA1 and LHY participates in the systems involved in sensing long-term cold for the activation of VIN3 transcription. Abstract : CCA1 and LHY bind to VREVIN3 in the VIN3 promoter to induce its transcription during vernalization.